2017
DOI: 10.1044/2017_jslhr-s-17-0081
|View full text |Cite
|
Sign up to set email alerts
|

Neural Indices of Semantic Processing in Early Childhood Distinguish Eventual Stuttering Persistence and Recovery

Abstract: ERPs elicited in 5-year-old CWS-eRecovered compared with CWS-ePersisted suggest that future recovery from stuttering may be associated with earlier maturation of semantic processes in the preschool years. Subtle differences in ERP indices offer a window into neural maturation processes for language and may help distinguish the course of stuttering development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 90 publications
4
8
0
1
Order By: Relevance
“…For both TD and SSD groups, the N400 effect for violations in lexical expectations was distributed over anterior and posterior ROIs. This broad distribution of the N400 is consistent with previous investigations of language processing in young children with TD (e.g., Atchley et al, 2006;Byrne et al, 1999) and children with stuttering and SLI (e.g., Kreidler et al, 2017;Pijnacker et al, 2017). As children age, the distribution of the N400 becomes more focal, and this topographic change is thought to reflect more efficient, adultlike processing of semantic information (Atchley et al, 2006;Byrne et al, 1999;Holcomb et al, 1992).…”
Section: Lexical Processingsupporting
confidence: 89%
“…For both TD and SSD groups, the N400 effect for violations in lexical expectations was distributed over anterior and posterior ROIs. This broad distribution of the N400 is consistent with previous investigations of language processing in young children with TD (e.g., Atchley et al, 2006;Byrne et al, 1999) and children with stuttering and SLI (e.g., Kreidler et al, 2017;Pijnacker et al, 2017). As children age, the distribution of the N400 becomes more focal, and this topographic change is thought to reflect more efficient, adultlike processing of semantic information (Atchley et al, 2006;Byrne et al, 1999;Holcomb et al, 1992).…”
Section: Lexical Processingsupporting
confidence: 89%
“…Many theorists have concluded that experimental and clinical evidence related to the onset and development of stuttering in childhood points to the central roles played by speech motor, language, and emotional factors (Walden et al, 2012; Ambrose et al, 2015; Smith and Weber, 2017). Experimental evidence supports the critical roles of speech sensorimotor systems and the mediating effects of language processes in early childhood stuttering (Silverman and Ratner, 2002; Anderson et al, 2005; MacPherson and Smith, 2013; Weber-Fox et al, 2013; Spencer and Weber-Fox, 2014; Walsh et al, 2015; Kreidler et al, 2017; Usler et al, 2017). Our understanding of how emotional factors may affect speech production in stuttering, especially in early childhood, is far more limited.…”
Section: Introductionmentioning
confidence: 79%
“…Kreidler and colleagues 8 used ERPs as an index of semantic processing in 5-year-old CWS-eP, CWS-eR, and CWNS while they listened to sentences presented in a story con-text. Most of the CWS-eR exhibited a more mature pattern of ERP responses, similar to those seen in adult listeners, compared with CWS-eP.…”
Section: Experimental Level: Neurobiological Clues Into the Processesmentioning
confidence: 99%